Potential attenuation of early-life overfeeding-induced metabolic dysfunction by chronic maternal acetylcholinesterase inhibitor exposure. (1st September 2019) - Valério Prates, Kelly; Ribeiro, Tatiane Aparecida; Pavanello, Audrei; Jacinto Saavedra, Lucas Paulo; Moreira, Veridiana Mota; da Silva Silveira, Sandra; Martins, Isabela Peixoto; Francisco, Flávio Andrade; Ferreira Junior, Marcos Divino; Alves, Vander Silva; Tófolo, Laize Peron; Previate, Carina; et al.
Abstract: Evidence suggests that low concentration perinatal exposure to environmental contaminants, such as organophosphate (OP) is associated with later life insulin resistance and type 2 diabetes. The aim of this work was to investigate whether chronic maternal OP exposure exacerbates metabolic dysfunctions in early-overfed rats. During pregnancy and lactational periods, dams received OP by gavage. To induce neonatal overnutrition at postnatal day 3, pups were standardized to 9 or 3 per nest. At 90-days-old, glucose-insulin homeostasis and insulin release from pancreatic islets were analyzed. While both OP exposure and overfeeding alone did induce diabetogenic phenotypes in adulthood, there was no exacerbation in rats that experienced both. Unexpectedly, the group that experienced both had improved adiposity, metabolic parameters, attenuated insulin release from isolated islets in the presence of glucose and low function of muscarinic acetylcholine receptor M3, as well as an attenuation of beta cell mass hyperplasia. High levels of butyrylcholinesterase and low levels of insulin in milk may contribute to the OP-induced developmental programming. Our study showed that maternal OP exposure may program insulin release as well as endocrine pancreas structure, thus affecting metabolism in adulthood. Our data suggest that while perinatal OP exposure alone increases the risk for later life T2D, it actually reverses many of the programmed metabolic dysfunction that is induced by postnatal overfeeding. These surprising results may suggest that low-dose administration of acetylcholinesterase inhibitors could be of utility in preventing detrimental developmental programming that is caused by early-life overnutrition.